Determination of Community Value Representation to Improve Sustainable Performance of MSMEs Grape Sellers in Indonesia - Wilis, Ratih Anggoro; Efendi, Suryono; Nurwulandari, Andini (International Review of Management and Marketing, 2026)
The main objective of this study is to analyze the influence of Entrepreneurial Orientation (EO) and Digital Capability (DC) on SMEs Sustainable Performance (SP) through Competitive Advantage (CA) as an intervening variable and Community Value Representation (CVR) as a moderating variable, which is the novelty of this study among Grape entrepreneurs in Indonesia. Specifically, this research is present as an effort to fill the gap in the limited literature on the role of Community Value in maintaining the sustainable performance of Grape sellers in Indonesia who are members of the Indonesian Grape Entrepreneurs Association (ASPAI). A total of 264 grape sellers participated as respondents in this study, who are members of the Indonesian Grape Entrepreneurs Association (ASPAI), using the sample determination technique of Hair et al. The method used was the quantitative method using SEM-PLS. Based on the research findings, EO encourage the strengthening of SP significantly. DC unable to prove any influence on SP. CA gave positive effect on SP. EO and DC have a significant positive effect on CA. EO and DC have a significant indirect positive effect on SP through CA. CVR positively mediates DC to CA, but not EO to CA.